"Золоті татарські, турецькі, язичні; флорини землі нашої": до проблеми таємничого монетарного терміна XV - XVII ст. - Огуй, О. (Інститут історії України НАН України, 2009)
This article deals with a mysterious coin denomination of Bukovyna and Moldova (XV - XVII centuries), known as “Tartarian zlot”. Investigation of certain cancellers of neighboring states and cities (Lviv, Brasov, Bistritz) resulted in synonymous denominations “heidnische Gulden, zloti valaski, moldawski; fl. terre nostre”. The author proves that Tartarian zlot (heidnische Gulden,etc.) was equal to 12 asprs. The given counting system of Bukovyina was borrowed in Byzantine and impacted by counting systems of Pont & Golden Horde.